PEMETAAN OBYEK WISATA ALAM DI KABUPATEN TANGGAMUS PROPINSI LAMPUNG - Amar Daumi; I Gede Sugiyanta; Dedy Miswar (JPG (Jurnal Penelitian Geografi), 2013)
This research purposed to know the kind of natural tourism object, the spread natural tourism object, the potential particularly from natural tourism object which there in Tanggamus Regency with away made natural tourism object of map at tanggamus regency 2012.The method of this research was applied which purposed so that the result could be used or could be implemented. The collecting of data was done through measuring directly at sphere which was enclosed interview was not structure and documentation.The result of this research was digital map of natural tourism object Tanggamus Regency with system information of geography which was used as media helping for tourist to get the information of natural tourism object at Tanggamus Regency. The conclusion in this research was the spread of natural tourism object with used system SIG could be easy to see the spread natural tourism object at Tanggamus Regency of 2012 in form regular map and digital map.Key Word: mapping, natural tourism object, GIS